Aliens and existential elevators: absurdity and its shadows in Douglas Adams’s Hitch hiker series - M.A. van der Colff (Literator, 2008)
According to twentieth-century existentialist philosophy, the universe as we know it is steeped in senselessness, and the only possible means of survival is the construction of subjective meaning. Douglas Adams’s fictional universe portrayed in his “Hitch hiker” series reflects the arbitrary nature of existence, and the characters dwelling in this narrative space are faced with two existential choices: the one is defiance in the face of senselessness, the other is bleak despair. This article explores the existential choices made by prominent characters in the “Hitch hiker” series. The article distinguishes between and analyses the Sisyphus characters and their polar opposites (or nihilist shadows) in Douglas Adams’s “Hitch hiker” series. Adams’s characters, be they human, alien or sentient machine, all face the same existential choice: actuate individual meaning, or resort to despondency. Characters who choose the first option are regarded as Sisyphus figures, whereas characters who choose the latter are referred to as shadows or nihilist nemeses.